2001
DOI: 10.1081/pfc-100103568
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethrins and Piperonyl Butoxide Residues on Potato Leaves and in Soil Under Field Conditions

Abstract: Residues of pyrethrin-I (Py-I) and pyrethrin-II (Py-II), the major insecticidal components of the pyrethrum daisy (Tanacetum cinerariifolium) as well as residues of piperonyl butoxide (PBO, a pyrethrum synergist) were determined in soil and on potato foliage grown under field conditions. A pyrethrum formulation (Multi-Purpose Insecticide) containing the three active ingredients was sprayed twice at the rate of 6 lbs of formulated product.acre(-1) ( 5.4 and 27.2 g A.I. of pyrethrin and PBO, respectively) on pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
11
2
Order By: Relevance
“…Isolute C 18 cartridges (Isolute, International Sorbent Technology Ltd., MID Glamorgan, UK) of 500 mg octadecyl were placed on a solidphase extraction vacuum manifold (Alltech, Deerfield, IL) and conditioned first with 6 mL of methanol followed by 6 mL of water according to the methods described by Antonious et al [2] The filtered samples were loaded onto the cartridges and passed through at a flow rate of 1-2 mL min À1 . After 24 h, samples were filtered through Whatman 934 AH glass microfiber discs of 55 mm diameter (Fischer Scientific, Pittsburgh, PA).…”
Section: Batch Equilibrium Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Isolute C 18 cartridges (Isolute, International Sorbent Technology Ltd., MID Glamorgan, UK) of 500 mg octadecyl were placed on a solidphase extraction vacuum manifold (Alltech, Deerfield, IL) and conditioned first with 6 mL of methanol followed by 6 mL of water according to the methods described by Antonious et al [2] The filtered samples were loaded onto the cartridges and passed through at a flow rate of 1-2 mL min À1 . After 24 h, samples were filtered through Whatman 934 AH glass microfiber discs of 55 mm diameter (Fischer Scientific, Pittsburgh, PA).…”
Section: Batch Equilibrium Techniquementioning
confidence: 99%
“…[1,2] Safe and effective biodegradable pest control chemicals with greater selectivity are needed. Adsorption may reduce the concentrations of pesticides in the soil solution, decrease their bioavailability, increase their rates of chemical degradation by soil microorganisms, or decrease their mobility into runoff and infiltration water.…”
Section: Introductionmentioning
confidence: 99%
“…Antonious et al (2001) similarly found the K ow for pyrethrin I (416,869) to be higher than the more soluble than pyrethrin II (3,631). The estimated bioconcentration factor (BCF) data, the ratio of the concentration of a chemical in an animal to that in the animals environment, are also consistent with the solubility and K ow results, with higher BCF for the more lipophilic group I pyrethrins.…”
Section: Watermentioning
confidence: 64%
“…It was also determined by Antonious et al (2004) that increasing the humic acid concentration significantly reduced the mobility of pyrethrins. Further, Antonious et al (2001) found that compost with high organic matter content absorbed more of pyrethrin I (0.056 µg/g) than no-mulch (0.026 µg/g) and fescue strip soils (0.002 µg/g) in potato field trials. The study indicated that pyrethrin I bound strongly to soils (K oc = 26915) while pyrethrin II did not (K oc = 2042).…”
Section: Soils and Microbial Interactionsmentioning
confidence: 99%
“…This is due to their short persistence in the environment (Antonious et al 1997(Antonious et al , 2001Angioni et al 2005), high level of potency against a wide range of arthropods (Burgess et al 1988), low application rate, and low toxicity to most vertebrates with the exception of fish (Edwards et al 1987, Croft et al 2001. Therefore, these insecticides are frequently the compounds of choice for use in agricultural and residential environments, and it is essential to evaluate the capabilities of the various forms of pyrethroids commercially available.…”
Section: Introductionmentioning
confidence: 99%